Evaluasi Kebijakan Penertiban Perparkiran di Kawasan Wisata Religi Sunan Ampel: Studi Kasus Jalan Nyamplungan, Kota Surabaya - Zeni Fradita Sari; Dewi Arimbi Burhandani Piliang; Nabil Nazhif Fikri Ahmad; Muhammad Chairil Umam; Muhamad Fatih Eko Cahyo; Tauran; Wilda Sumarsyah (Universitas Mbojo Bima, 2026)
The problem of illegal parking in the Sunan Ampel religious tourism area in Surabaya has become a complex issue due to the high mobility of visitors not being matched by the availability of adequate parking space. This condition requires an evaluation of parking control policies to support the achievement of the Sustainable Development Goals (SDGs). This study aims to analyze the implementation of illegal parking control policies and identify obstacles that arise during their implementation. The research approach uses a qualitative method with case studies through interviews, observation, and documentation techniques. Data analysis was conducted using the OECD DAC evaluation framework, which includes relevance, coherence, effectiveness, efficiency, impact, and sustainability. The results show that parking control policies have a strong legal basis and are supported by inter-agency coordination. However, their implementation is not optimal because illegal parking practices still occur due to limited parking facilities, low public awareness, and the economic factors of informal parking attendants. In addition, the suboptimal use of digital technology and monitoring systems affect the effectiveness of the policy. Therefore, strengthening collaboration between stakeholders and empowering the informal sector is necessary. These efforts are expected to create orderly traffic, improve tourist comfort, reduce potential losses of Regional Original Revenue, and encourage the sustainability of parking enforcement policies in the Sunan Ampel religious tourism area in Surabaya.